2006
DOI: 10.1111/j.1439-0434.2006.01127.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic and Genetic Variability within Macrophomina phaseolina from Mexico and Other Countries

Abstract: Pathogenic and genetic characterizations of 96 isolates of Macrophomina phaseolina from Mexico and other countries were carried out in order to define the pathogenic and genetic patterns of diversity and to gain insights into the pathogenic and genetic specialization in this fungus. Isolates were collected from different hosts in Mexico (23 isolates), Italy, Australia, Japan, Argentina, USA, Colombia and Brazil (73 isolates). Pathogenicity was evaluated in seeds of two Phaseolus vulgaris L. cultivars under in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…A number of molecular studies elsewhere have shown a high level of polymorphism in this fungus when isolates from different host or geographical origins were compared using different molecular tools (Almeida et al, 2003;Jones et al, 1998;Mayek-Perez et al, 2001;Su et al, 2001;Vandemark et al, 2000). Other recent studies have demonstrated the genetic diversity among M. phaseolina isolates (Aboshosha et al, 2007;Aghakhani and Dubey, 2009;Babu et al, 2010;Baird et al, 2010;Beas-Fernandez et al, 2006;Das et al, 2006;Jana et al, 2005a;Jana et al, 2005b;Omar et al, 2007;Purkayastha et al, 2008;Rajkumar and Kuruvinashetti, 2007;Reyes-Franco et al, 2006;Saleh et al, 2010). The high genetic diversity of this pleomorphic fungal species is reflected not only in isolates from distinct hosts and geographical origins but also within isolates collected from a single host or geographical origin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of molecular studies elsewhere have shown a high level of polymorphism in this fungus when isolates from different host or geographical origins were compared using different molecular tools (Almeida et al, 2003;Jones et al, 1998;Mayek-Perez et al, 2001;Su et al, 2001;Vandemark et al, 2000). Other recent studies have demonstrated the genetic diversity among M. phaseolina isolates (Aboshosha et al, 2007;Aghakhani and Dubey, 2009;Babu et al, 2010;Baird et al, 2010;Beas-Fernandez et al, 2006;Das et al, 2006;Jana et al, 2005a;Jana et al, 2005b;Omar et al, 2007;Purkayastha et al, 2008;Rajkumar and Kuruvinashetti, 2007;Reyes-Franco et al, 2006;Saleh et al, 2010). The high genetic diversity of this pleomorphic fungal species is reflected not only in isolates from distinct hosts and geographical origins but also within isolates collected from a single host or geographical origin.…”
Section: Resultsmentioning
confidence: 99%
“…However, usually isolates from the same host or origin tend to group together. Several studies have found no association between DNA genotype and host origin in populations (Almeida et al, 2003;Reyes-Franco et al, 2006;Vandemark et al, 2000). Recently Saleh et al (2010) used AFLP markers and ITS region sequences to assess the genetic diversity and relationships of M. phaseolina isolates from maize, sorghum, tallgrass prairie and soybean.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been observed for many bean pathogens such as rust Sandlin et al (1999); Mmbaga et al 1996a), anthracnose (Ansari et al 2004;Balardin et al 1997), web blight caused by Thanatephorus cucumeris (Godoy-Lutz et al 2003), angular leaf spot caused by Phaeoisariopsis griseola (Mahuku et al 2002;Pastor-Corrales et al 1998) and ashy stem blight caused by Macrophomina phaseolina (Tassi) Goid. (Reyes-Franco et al 2006).…”
Section: A Few Examples Of Conventional Bean Breeding Achievements Inmentioning
confidence: 95%
“…Ashy stem blight exhibits significant morphological, physiological, pathogenic and genetic variability which makes the pathogen more capable of adapting and attacking susceptible hosts in diverse environments. Diversity in M. phaseolina is due to the heterokaryotic condition of mycelium as well as the presence of two asexual sub-phases, one saprophytic (R. bataticola) where microsclerotia and mycelia are mainly produced and another pathogenic [7,8] where microsclerotia, mycelia and pycnidia are produced in host tissues.…”
Section: Introductionmentioning
confidence: 99%